Ion beam science : solved and unsllved problems - Sigmund, Peter (Matematisk-fysiske meddelelser, 2006)
Part. I: Ion-solid interactions in astrophysics - Hadron therapy: radiotherapy using fast ion beams - Spatial distribution of DNA Double-Strand Breaks fron ion track - Magnetic confinement fusion: ions in ITER-beams and surfaces - High energy density matter generated by heavy-ion beams and application to fusion energy - Ion beam analysis of lower dimensional structures - Solved and unsolved problems in ion-beam analysis: the influence of single collisions - Nanoscale moorphology control using in beams - Ion-induced surface evolution in the linear instability regime: continuum theory and kinetic Monte Carlo simullation - Some ion-beam modification issues: ion-induced amorphisation and crystallisation of silicon - Experimental phenomena and thermal spike model description of ion tracks in amorphisable inorganic insulators - Thermal-spike models for ion track physics: a critical examination - Some solved and unsolved problems in transmission electron microscopy studies of radation damage in solids - Radiation damage in carbon nanotubes: what is the role of electronic effects. - Part II: Ion beam-induced amorphization: a crystal to glass transition? - Sputtering: experiment - Sputter theory - A critical review of the electron-tunnelling models of secondary ion formation - Electron emission from solids irradiated with swift ion beams - Recent advances in slow heavy particle induced electron emission - Stopping of swift ions: solved and unsolved problems - Charge states and energy loss of ions in solids - Charge transfer in atom-surface interactions - Channeling and blocking of energetic charged particles in crystals - Penetration phenomena at relativistic energies - Early history of ion beam physics.